Análisis de los costos de ventas y gastos operacionales de la empresa Ruvicoa de la ciudad de Babahoyo - Alvarez Muñoz, Allinson Madeline (2021)
Ruvicoa is an industrial and agricultural company that is dedicated to the production, marketing, distribution and export of cocoa, coffee, tea and spices to all regions of Ecuadorian nationality and to various countries in the world. The present case study called "Analysis of the costs of sales and operating expenses of the Ruvicoa Company of the city of Babahoyo", aims to analyze and compare the costs of sales and operating expenses for 2019 and 2020, for this, it is He proceeded to calculate the absolute and relative variations of the two periods. Sales costs reflect the investment represented in all expenses that were made or used in a product, good or service. On the other hand, the operational expenses of a company are called as those that represent the sum of all the expenses incurred by the company or organization, to develop the daily functions or activities and thus be able to generate income. Finally, the research was carried out applying the descriptive and exploratory methodology, by collecting bibliographic information, and in turn, conducting an interview with the Accountant and Owner of the company.